Pengembangan Usaha Mikro Kecil Menengah (Umkm) Menjadi Perusahaan Go Public - RACHMAWATI, NINDA; SUKMAWATI, SARI (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2025)
The purpose of this study is to discuss financial management related to how to create and maintain economic value or wealth. Economic decisions should also focus on wealth creation. Financial management is the management that links acquisition, expenditure or financing, and asset management with the overall goals of the company. The function of financial management is fundraising, which aims to make useful decisions. This fund management activity aims to control the use of funds for company activities, small businesses, SMEs, or MSMEs, increase job opportunities, inherit various economic services for the community, and act when the justice process increases community income, rejects economic growth, and reaches regional goals. Development is a solution implemented by the government, business forums, and the community by providing guidance and support to help staff grow and improve the ability of SMEs to become proven and independent companies.